The detailed geological investigation in Kadidia geothermal field and surrounding areas, Nokilalaki District, Sigi Regency, Central Sulawesi Province - Firmansyah, Irwan; Siswandi, Siswandi; Iswahyudi, Sachrul; Hermawan, Dudi; Mustofa, Santia Ardi (Journal of Earth and Marine Technology (JEMT), 2022)
The need for alternative energy other than fossil energy is felt to be increasingly urgent for the fulfillment of domestic electrical energy. In meeting the demand for electricity, the government needs to investigate alternative geothermal energy, to find out the potential for geothermal energy to provide electricity. The realization of this policy is that the government conducts an integrated geothermal investigation to find prospective geothermal areas that can be developed as electric power. Nokilalaki District, Sigi Regency, Central Sulawesi Province is one area that has geothermal potential in Indonesia. The Kadidia geothermal area, Sigi Regency, Central Sulawesi Province is one of the volcanic geothermal fields that have good potential and needs to be investigated further, especially on geological conditions that affect the presence of geothermal energy. The research method used is the method of analyzing the results of field observations. From the observations, it can be concluded that the geomorphology of the research area is divided into Tongoa hills, Nokilalaki Granite Intrusions, Kamamora Hills, and Kadidia Alluvial Plains. The stratigraphy of the study area from old to young consists of Breccia, Sandstone, Granite Intrusion A, Granite Intrusion B, Granite Intrusion C, and Alluvial Plain. The geological structure of the study area consists of the Kamamora sinistral shear fault and the Kadidia dextral shear fault. The geological history of the study area begins in the early Miocene which is the beginning of the movement of the Palu - Koro fault.